Analysis of the Implementation of the Occupational Health and Safety Management System at PT Aneka Tambang Tbk. Gold Mining Business Unit (GMBU) Pongkor, Bogor West Java 2020 - rizki adam; rijal abdullah (Journals Mining Engineering : Bina Tambang, 2021)
ANTAM has a full commitment to implement good mining practices in every operational activity of the Company. In performing every mining activity, ANTAM always considers the technical aspects & standardization of mining operations, conservation of mineral resources, commitment in maintaining occupational health & safetyof control method, namely elimination, substitution, engineering control, administrative control, and PPE. All mining safety statistics in 2010-2020 show safety performance statistics of ANTAM and its subsidiaries/ sub subsidiaries: 8 fatal accident, 24 serious accident and 47 (one) minor accident, frequency rate level FR: 25,12, ANTAM’s Severity Rate/ SR 214.06. TRIR (Total Recordable Incident Rate): 0.01. ANTAM always prioritizes the implementation of occupational health and safety principles in every operation of the Company. ANTAM constantly attempts to manage mining safety by proper standards and regulations. We have also classified the types of high risk activity in the Company’s workplace. The commitment to implement Occupational health and safety has brought good results. Antam managed to maintain a positive trend decline in the number of occupational accidents cases.